Prevalence and clinical characteristics of urinary incontinence in elderly individuals of a low income - Burti, Juliana Schulze; Santos, Adriana M. Barsante; Pereira, Rosa Maria R.; Zambon, João Paulo; Marques, Amélia Pasqual (Elsevier, 2012)
To estimate the prevalence of urinary incontinence (UI) in elderly individuals of low income assisted by the primary health care system in São Paulo, Brazil. In this community-based, observational, cross-sectional study, participants assisted by the health family program in São Paulo, Brazil, were sampled and interviewed face to face by questionnaire. Participants (n= 388) were selected from the collaborative program developed by the 10/66 Dementia Research Group, an International Network of investigators. Demographics, health history and a detailed assessment of UI and urinary symptoms were obtained. Prevalence of UI was calculated. Other variables included age, body mass index (BMI), duration of incontinence and characteristics of the symptoms. The association between UI and the variables was estimated using the Kruskal-Wallis test, Chi-squared test and Fisher test (depending on normality of the distribution and expected frequencies). Prevalence of UI was 38.4%. UI was more common in women than in men (50% vs. 18.3%, p< 0.001). Diabetes, obesity and hypertension were associated with UI. Almost 36.2% of the cases were of mixed incontinence, 26.8% of urge incontinence and 24.2% of stress incontinence. Men were more likely to have urge-incontinence, while women were more likely to have mixed incontinence (p= 0.001). UI is prevalent in the elderly of low income living in São Paulo and rates are higher than most previous studies. Chronic conditions such as hypertension, diabetes and obesity were associated with UI. © 2011 Elsevier Ireland Ltd.
Keywords: Elderly; Low socioeconomic status; Prevalence; Urinary incontinence